Wakaf Dan Pengembangan Pendidikan Islam Di Indonesia - Mutmainah Mutmainah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2017)
Islamic waqf system caused by the economic system of Islam, which considers that the economy is closely linked with theology and Islamic law, as well as the balance between the economy and the benefit of society. Endowments can be a source pendaaan of the people for the people, either for religious, social, and economic. For the understanding of the function of waqf should be socialized and become a collective movement of the whole society in order to improve the economy of the people. Waqf institutions become a financial source for Islamic educational institutions. Optimal utilization of endowments to help the government in the welfare of the people because if the endowment is managed properly it will greatly support the development, both in the field of education, economic, religious, social, cultural, political, and defense and security. In the management of waqf, not only to be done in a professional manner but also transparent and accountable. Both of these factors should be embodied in the management of waqf property because the property that have endowments will move belongs to the people. Thus professional management, transparency and accountability, the Waqif right to correct information, clearly dn honest about the conditions that have been waqf property.